Taxonomic and Metabolic Incongruence in the Ancient Genus Streptomyces - Chevrette, Marc G.; Carlos-Shanley, Camila; Louie, Katherine B.; Bowen, Benjamin P.; Northen, Trent R.; Currie, Cameron R. (Frontiers in Microbiology, 2019)
The advent of culture independent approaches has greatly facilitated insights into the vast diversity of bacteria and ecological importance they hold in nature and human health. Recently, metagenomic surveys and other culture-independent methods have begun to describe the distribution and diversity of microbial metabolism across environmental conditions, often using 16S rRNA gene as a marker to group bacteria into taxonomic units. However, the extent to which similarity at the conserved ribosomal 16S gene correlates with different measures of phylogeny, metabolic diversity, and ecologically relevant gene content remains contentious. Here, we examine the relationship between 16S identity, core genome divergence, and metabolic gene content across the ancient and ecologically important genus Streptomyces. We assessed and quantified the high variability of average nucleotide identity and ortholog presence/absence within Streptomyces, even in strains identical by 16S. Further, we identified key differences in shared ecologically important characters, such as antibiotic resistance, carbohydrate metabolism, biosynthetic gene clusters, and other metabolic hallmarks, within 16S identities commonly treated as the same operational taxonomic units (OTUs). Differences between common phylogenetic measures and metabolite-gene annotations confirmed this incongruence. Our results highlight the metabolic diversity and variability within OTUs and add to the growing body of work suggesting 16S-based studies of Streptomyces fail to resolve important ecological and metabolic characteristics.